Perspektif Teori Komunikasi Menurut B. Aubrey Fisher dalam Kajian Komunikasi Islam - Timur Tumanggor; Rubino; Mailin (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to explain B. Aubrey Fisher's perspective on communication theory as a dynamic conceptual process. It analyzes the key concepts in his theory, particularly those related to meaning formation, and examines their relevance and application in understanding contemporary communication phenomena. The study employed a qualitative approach using library research. Data were obtained from Fisher's key works, as well as relevant communication theory literature and recent research. Data analysis was conducted through qualitative content analysis with an interpretive and contextual approach. The results indicate that Fisher's communication theory places meaning at the core of the communication process, which is inherently non-final, dynamic, and contextual. Meaning is understood as the result of conceptualizing raw experience through language and symbols, so differences in interpretation and the potential for misunderstanding are inherent parts of communication. Furthermore, Fisher's theory has proven relevant in explaining contemporary communication phenomena, particularly in the context of digital communication, the polarization of meaning, and active audience participation. Thus, B. Aubrey Fisher's communication theory provides a significant theoretical contribution to enriching modern communication studies that focus on process, meaning, and social context